TEMPERATURE ANALYSIS OF A FLAT SOLAR COLLECTOR USING ALUMINUM NANOFLUIDS - Murat Kunelbayev; Stepan Vyazigin; Erol Kurt (Вестник КазНУ. Серия математика, механика, информатика, 2022)
In this work, the thermal characteristics of a flat solar collector were performed using a nanofluid of aluminum oxide- water. The purpose of this article is to develop a hydrodynamic model using the CFD program. The main direction of the study is that the model is confirmed by the results of the experiment conducted in this study. The model is modeled in the temperate climate of Kazakhstan. The idea of the scientific research was that with the help of the ANSYS FLUENT 19.0 CFD (Computational Fluid Dynamics) package, to calculate the presence of nanoparticles in the working fluid of a flat solar collector increases the pressure drop in a flat solar collector, but also an increase in thermal characteristics is achieved. It has been experimentally established that the optimal volume fraction of nanoparticles, which is 0.5% aluminum oxide, provides the greatest thermal efficiency of a flat solar collector. A new design of a flat solar collector has been developed, in which thermal insulation occurs in a heat-insulating transparent double-glazed window. The data on the temperature of the flat solar collector were determined using the commercial software package CFD (Computational Fluid Dynamics) ANSYS FLUENT 19.0. Numerical analysis of temperature data confirmed the accuracy of the results obtained as a result of experimental analysis. The practical significance of the results of this work suggests that the presence of nanoparticles on the upper glass of the collector increases thermal efficiency, efficiency and service life.